KESULITAN BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA MATERI OPERASI HITUNG - Dwi Ariyanti, Mei Riska; Dini Rakhmawati; Arri Handayani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The aim of this research is to find out how to diagnose/find out students' learning difficulties and find out solutions to overcome/solve the problem of learning difficulties from students' daily tests in mathematics subjects, especially in mixed arithmetic operations material. The subjects of this research were 23 students. Researchers conducted three written tests to diagnose/find out students' learning difficulties in mixed arithmetic operations in the first daily test, there were 8 students (34.7%) who were able to understand and determine which ones were known and which ones were asked, while 15 students (65.3%) %) don't understand. In the second daily test, 10 students (43.5%) were able to understand and determine what was known and what was asked, while 13 students (56.5%) did not understand. In the 3rd daily test, 3 students (13%) were able to understand and determine what was known and what was asked, while 20 students (87%) did not understand. To provide assistance to students who experience difficulties in learning, researchers take the following steps: (a) The teacher carries out an initial diagnosis in learning; (b) Teachers can understand children's psychological conditions; (c) Teachers can group students based on students' characteristics, abilities and learning styles in following the learning process; (d) Teachers use fun learning models and methods. Keywords: Diagnosis of Learning Difficulties, Mathematics, mixed arithmetic operations